Analisis Yuridis Perkara Tindak Pidana Pendudukan dan Pencurian di Perkebunan PT Fajar Pematang Indah Lestari (Studi Kasus Putusan Pengadilan Negeri Sengeti Nomor 94/Pid.Sus/2023/Pn Snt) - Yudhanto, Febri; Nggeboe, Ferdricka; Supeno, Supeno (Legalitas: Jurnal Hukum, 2025)
The Unitary State of the Republic of Indonesia is a Republic based on law as affirmed in the 1945 Constitution of the Republic of Indonesia Article 1 Paragraph (3). Land issues have become a very important issue in Indonesia. An example of a criminal case in the land sector is the criminal case of occupation and theft in the PT FPIL Plantation as decided in Decision Number 94/Pid.Sus/2023/Pn Snt. This problem occurred against the background of several meetings and mediations, with no agreement/solution reached between PT FPIL and the Sumber Jaya Village Community. In the decision in question, the judge's consideration has not considered non-juridical factors such as social factors, economic factors of the perpetrator and factors of corporate responsibility towards the community in the trial facts. In the application of the law, the panel of judges at the Sengeti District Court handed down an ultra petita verdict (sentencing more than the charges) and the verdict was still too severe considering that the defendant and the community had actually made good intentions by asking PT FPIL for help, but PT FPIL did not provide assistance. During the meeting and mediation, no agreement/solution was reached between PT FPIL and the defendant and the Sumber Jaya Village Community on the issue in question. Therefore, the judge's verdict, which only imposed 1 (one) year and 6 (six) months imprisonment, is considered to still not reflect social justice for the defendant.